Support scull techniques in elite synchronized swimmers - Homma, Mi.; Homma, Ma. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to investigate support scull techniques in synchronized swimming based on three-dimensional motion analysis. The support scull movements of ten elite synchronized swimmers were analyzed using a three-dimensional \ DLT method. It was found that support scull is a lever movement made from the elbow that produces propulsive force by generating drag force during the outside transition phase and lift force during both out-scull and in-scull of the horizontal stroke phases. To scull in a smoother and more stable performance, swimmers should hold their elbows and upper arms stationary and keep their forearms horizontal during sculling. Palms should face downwards throughout sculling and hands should be held at the proper attack angle to produce an efficient lift force.